Genome Characterization of Carbapenem-Resistant Hypervirulent Klebsiella pneumoniae Strains, Carrying Hybrid Resistance-Virulence IncHI1B/FIB Plasmids, Isolated from an Egyptian Pediatric ICU - Heba A. Hammad; Radwa Abdelwahab; Douglas F. Browning; Sherine A. Aly (Microorganisms)
Despite the increased reporting of Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKp) in Egypt, there is a paucity of information regarding the molecular characteristics of such strains. Herein, we present the genome sequence of two CR-hvKp strains, K22 and K45, which were isolated from VAP (ventilator-associated-pneumonia) patients admitted to pediatric ICU at Assiut University Children’s Hospital, Egypt. K22 and K45 isolates were subjected to antimicrobial susceptibility testing and whole-genome sequencing. Genomic analysis was performed to characterize each strain, determining their plasmids, antimicrobial resistance (AMR) genes, and virulence determinants. K22 possessed an extensive drug resistance phenotype (XDR), whilst K45 exhibited a multidrug resistance phenotype (MDR), with genome sequencing revealing the presence of a diverse array of AMR genes. Both strains were resistant to the carbapenem antibiotic imipenem, carrying the OXA-48 carbapenemase, with K22 additionally possessing an NDM-1 carbapenemase. Each strain was considered high-risk, with K22 and K45 respectively belonging to sequence types ST383 and ST14 and possessing virulence genes implicated in hypervirulence (e.g., iucABCD-iutA and rmpA). Importantly, both strains carried multiple plasmid replicons, including an AMR/virulence IncHI1B/FIB hybrid plasmid and MDR IncL/M plasmids. This report highlights the critical role of plasmids in the evolution of virulent K. pneumoniae strains and suggests the circulation of an IncHI1B/FIB hybrid plasmid, simultaneously disseminating AMR and hypervirulence, amongst K. pneumoniae strains within Assiut University Children’s Hospital.